THE USE OF CASE TECHNOLOGY IN TEACHING ENGLISH LANGUAGE - Mukhammadieva, Shokhsanam; Makhmudova, Mohina (Educational Research in Universal Sciences, 2024)
Any assimilation of knowledge is based on the assimilation of learning actions by the student, having mastered which, the student would be able to assimilate knowledge independently, using various sources of information. To teach to learn, namely to assimilate and properly process information is the main thesis of the activity approach to learning. One of the new forms of effective learning technologies is problem-based learning using case studies. The introduction of case studies in teaching English into the practice of education is currently a very urgent task.